The Influence of Governance and Ownership on CSR Practices in Romania - Lelia Voinea, Cosmina; Fratostiteanu, Cosmin; Romein, Bas (European Journal of Sustainable Development, 2019)
Ownership structure represents the distribution of equity with regard to votes and capital but also by the identity of the equity owners. These structures are of major importance in corporate governance because they determine the incentives of managers and thereby the economic efficiency of the corporations they manage. This papers analyzes the relationship between governance, ownership structure and CSR practices among companies in Romania. The results of this study allows corporates and the public to formulate a well substantiated opinion on the way particular organizations carry out their businesses in Romania regarding CSR where CSR practices reflect culture and are partially county and ownership specific. The CSR practices implemented in Romania may not always reflect the societal views but rather the public ownership / government views, on what is thought to be important. Keywords: governance, ownership, emerging economies, Romania, corporate social responsibility, CSR practices